静脈内鎮静法下口腔外科小手術時の年齢による循環変動の特徴について - 金 博和; 高田 耕司; 岡 俊一; 見崎 徹 (Ronen Shika Igaku, 2010)
The purpose of the present study is to depict hemodynamic variability patterns by age on a display using a PC monitoring system by graphically plotting circulation changes during oral surgery under intravenous sedation.The subjects were 52 healthy patients who underwent oral surgery such as tooth extraction or cystectomy. They were divided into 3 groups according to age (20’s : Group 1, 40’s : Group 2, 60’s : Group 3).The patients’ Systolic Blood Pressure (SBP) and Pulse Rate (PR) were measured during surgery using an automatic blood pressure/pulse measuring device. Regulation of perioperative SBP and PR were plotted on the coordinate display of the personal computer, with the rate of PR as the parallel axis and the rate of SBP as the vertical axis, quadratically. In this study, the coefficient of variation of perioperative SBP (CVSBP), PR (CVPR), and the gradient of the regression line from obtained trace coordinate points were used as an index of hemodynamic variability during intravenous sedation.Intravenous sedation was performed using propofol. BIS monitor was used as an index of sedative state and the BIS value kept to around 80. For local anesthesia of the oral cavity, 2% lidocaine with 1 : 80,000 adrenalin was also used.In the comparison of the values during surgery between the 3 groups, the values in Group 1 for CVPR were significantly higher than those of Group 3, and the values in Group 3 for CVSBP were significantly higher than those of Group 1 and 2. The gradient of the regression line between the rate of change of PR and the SBP for Group 3 is greater than that of Group 1. This indicated that the regulation of PR is greater than that of SBP in Group 1, and the rate of SBP is greater than that of PR in Group 3. In other words, the trace on the graphic was pictured differently: in the bilateral direction in younger subjects, and in the vertical direction by in older subjects. 歯科治療時の循環変動をグラフィック化させるPCシステムを用いて, 静脈内鎮静法下口腔外科小手術時の年齢による循環変動の特徴について検討した。対象は, 抜歯術や嚢胞摘出術などを受けた20歳代, 40歳代, 60歳代の健常患者52例とした。プロポフォールによる静脈内鎮静法を併用し, 術前の基準値に対する術中, 術後の収縮期血圧 (SBP), 脈拍数 (PR) の変動率を二次元プロットした。座標点が軌跡する方向性を検討するために, SBP, PRから算出した変動係数 (CVSBP, CVPR) と, 座標点から算出した回帰直線の傾き (絶対値) を各年代で比較した。また, 術前に脈拍 (心拍) 変動解析 (HRV), 加速度脈波 (APG) を測定した。若年者では血圧に比べ脈拍数の変動が大きく, 加齢とともに脈拍数に比べ血圧の変動が大きくなり, グラフィック上で若年者では左右方向, 加齢に従い上下方向へと異なる軌跡が描かれた。すなわち, 加齢によりCVPRは小さく, CVSBPは大きくなり回帰直線の傾きは大きくなった。また, 術前のHRVおよびAPGは加齢により減少した。得られた軌跡に違いがみられた理由として, 加齢による自律神経活動の低下や血管の老化に起因することが考えられる。本システムによって循環変動を視覚的に描出することで, 健常患者が年齢ごとにどのような軌跡を描くかを把握することができ, 診療時のリアルタイムの全身状態の把握, 合併症の予測と早期発見の一助となる可能性が示された。